(untitled) (Fiep Bulletin - online, 2015)
The present study aims to evaluate the motor development of school’s first year of elementary school from different educational systems of the city of Mossoro. The sample consisted of 41 students in the age group 5-6 years, 20 males and 21 females, a state school, one municipal and one private. The methodological tool used was battery of tests of motor coordination for children (Körperkoordination Test für Kinder - KTK) of Kiphard and Schilling (1974) consists of four tests: on the balance beam, lateral jumps, platforms transfer and jump with one leg. The results indicated that male students from state school are more coordinated than those of municipal and private schools, while the female students in private schools had better motor coordination than the state and local school. The evaluation also shows that, overall, the three girls schools have better coordination than boys. We conclude that factors such as environment and inadequate space, lack of incentives and proper guidance can contribute to poor physical activity in children and consequently cause poor motor coordination.